2018
DOI: 10.1155/2018/5412478
|View full text |Cite
|
Sign up to set email alerts
|

Expanded CD133+ Cells from Human Umbilical Cord Blood Improved Heart Function in Rats after Severe Myocardial Infarction

Abstract: Pharmacological approaches are partially effective in limiting infarct size. Cell therapies using a cell population enriched with endothelial progenitor cells (EPCs) CD133+ have opened new perspectives for the treatment of ischemic areas after infarction. This preclinical study evaluated the effect of intramyocardial transplantation of purified or expanded human umbilical cord blood-derived CD133+ cells on the recovery of rats following acute myocardial infarction (AMI). Histology studies, electrocardiogram, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Knowing whether one of these two sources can have better results can help when choosing the best therapy or possibly combining the two. Studies have demonstrated the potential of MSCs and eCD133 + cells in treating acute or chronic heart disease and respiratory and renal diseases [ 20 , 21 , 22 , 23 , 24 ]. Studies suggest that the therapeutic effect of these cells is mediated by modulation of the immune system, paracrine factors and the release of EVs [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knowing whether one of these two sources can have better results can help when choosing the best therapy or possibly combining the two. Studies have demonstrated the potential of MSCs and eCD133 + cells in treating acute or chronic heart disease and respiratory and renal diseases [ 20 , 21 , 22 , 23 , 24 ]. Studies suggest that the therapeutic effect of these cells is mediated by modulation of the immune system, paracrine factors and the release of EVs [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several preclinical studies that have used the injection of endothelial progenitor cells [5, 26, 27] or expanded CD133 + cells [7, 28] directly into a damaged heart have shown improved global heart function and decreased cardiac fibrosis. Khan and coworkers [29] demonstrated that mouse ESC-derived exosomes injected directly into the MI border zone have the ability to enhance neovascularization and cardiomyocyte survival and reduce fibrosis postinfarction.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, CD133 + cells have been evaluated in clinical studies aiming to treat patients with myocardial infarction, therefore opening new avenues for the treatment of ischemic areas [5]. Within this context, our group recently reported that transplanted expanded CD133 + cells ameliorated the infarcted heart and were suitable for the regeneration of the vascular system in a preclinical study, demonstrating strong potential for vascular regeneration [7]. Despite the demonstrated capacity of CD133 + cells to integrate into ischemic tissues and contribute to healing by promoting local angiogenesis [5, 6, 8], some studies have also suggested that the beneficial effects exerted by these cells are more likely indirect and dependent on their paracrine activities, including the secretion of extracellular vesicles (EVs) [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…The EV components can participate not only in various physiological processes such as homeostasis, inflammation, immunological interactions, and angiogenesis, but also in pathophysiological conditions involved in the development of cancer and metastasis, autoimmune diseases, and infections of various types [ 13 , 14 , 15 , 16 , 17 , 18 ]. EVs isolated from stem and endothelial progenitors have been tested in several disease models and shown to protect and/or repair kidney, nervous and heart tissue after injury, among other tissues and organs [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. On the downside, however, EVs can also help in preparing the niche for metastases, for example [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our group had previously shown that expanded CD133 + cells (E-CD133) significantly improved cardiac function in rats after severe myocardial infarction [ 21 ]. The improvement observed was mostly due to the activity of their secretome, which seems to be related to the induction of angiogenesis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%